Food Protein-Induced Enterocolitis Syndrome Causing Hypovolemic Shock and Methemoglobinemia - Stefan W. Malin; Riad Lutfi; Matthew L. Friedman; Alicia M. Teagarden (Case Reports in Critical Care)
A 5-week-old previously healthy male presented with vomiting and diarrhea leading to hypovolemic shock and profound metabolic acidosis. He was subsequently found to have severe methemoglobinemia. The acidosis and shock improved with fluid resuscitation and methemoglobinemia was successfully treated with methylene blue. An extensive workup, including evaluations for infectious and metabolic etiologies, was unremarkable. However, a detailed dietary history revealed a recent change in diet, supporting a diagnosis of food protein-induced enterocolitis syndrome (FPIES). We present this case to highlight the importance of considering FPIES in an infant with vomiting and diarrhea, in the setting of a recent dietary change, leading to profound dehydration, metabolic acidosis, and methemoglobinemia. Diagnosis of FPIES, although difficult to make and one of exclusion, can be potentially life-saving.